Both-Ways: Learning from Yesterday, Celebrating Today, Strengthening Tomorrow - Ober, Robyn (The Australian Journal of Indigenous Education, 2009)
Abstract This paper will discuss “both-ways” as the philosophy which underpins course programs and operations at Batchelor Institute of Indigenous Tertiary Education, the only tertiary institution in Australia that caters exclusively to Indigenous students. This paper draws on recent research undertaken by the author focusing on the following questions: What is bothways philosophy? How is it being implemented as a teaching methodology at an Indigenous tertiary institution? What innovative practices, processes and activities can be celebrated as exemplary teaching practice? The notion of both-ways will be explored to ascertain how it is being translated into an effective teaching methodology that incorporates and embraces Indigenous knowledge into course curriculum, planning, delivery and evaluation.